(untitled) (Texas Journal of Medical Science, 2024)
Toxic hepatitis, an inflammatory condition of the liver caused by exposure to toxins, presents a significant health challenge. While conventional treatments focus on removing the causative agent and supporting liver function, the potential role of biologically active supplements (BAS) in managing and mitigating the effects of toxic hepatitis is gaining attention. This paper examines the current understanding of toxic hepatitis and the rationale for using BAS. It explores the types of BAS, including antioxidants, hepatoprotective agents, and anti-inflammatory compounds, that may offer therapeutic benefits in the context of toxic liver injury. The study analyzes the existing evidence regarding the efficacy, safety, and appropriate use of these supplements, highlighting the importance of a personalized and evidence-based approach. It also emphasizes the necessity of understanding potential interactions with conventional treatments and the need for further research to clarify the optimal role of BAS in the management of toxic hepatitis